La flavescencia dorada en los viñedos del Alt empordá (Girona) - Rahola, J.=700 1 Reyes, J.; Giralt, Ll.; Torres, E.; Barrios, G.
Resumenes (Es, En)
12 fig; 32 ref.
Keywords: ENFERMEDADES DE LAS PLANTAS; VIÑA; FLAVESCENCIA DORADA; FITOPLASMA; BACTERIA SIN PARED CELULAR